The role of context for the development of conversation and the construction of meanings in cartoons - DOI: 10.4025/actascilangcult.v31i2.6317 - Nobrega, Daniela Gomes de Araújo (Acta Scientiarum. Language and Culture, 2009)
This article discusses the role context plays in the development of any oral interaction. It is, thus, in light of the Interactional Sociolinguistic area that I analyze a cartoon of a son-father dialogue to uncover the implicit meanings derived from contextual information. The analysis showed that, although the context of situation itself might determine the verbal and nonverbal interlocutors’ choices, such interlocutors can also (re)create the context to fulfill their communicative intentions.